ISIS-1 2 デ カンソク サレタ VLF ソーサー ノ トクセイ d. ジキケン ナイ ノ ULF・VLF ハドウ ダイ1カイ キョクチ ニオケル デンリケン ジキ ソウゴウ カンソク シンポジウム PART 2 - 尾崎, 孝之; オザキ, タカユキ; 岩瀬, 政之; イワセ, マサユキ; 吉野, 赳夫; ヨシノ, タケオ; 松尾, 敏郎; マツオ, トシロウ; 福西, 浩; フクニシ, ヒロシ; OZAKI, Takayuki; IWASE, Masayuki; et al. (国立極地研究所, 1979)
P(論文) 第17次観測隊(1976-1977)の手によって,昭和基地においてISISのVLF広帯域テータがテレメトリー受信された.その磁気テープ記録を周波数分析することにより作成されたタイナミックスペクトラムからVLFソーサーについて以下の点が明らかとなった.1)ソーサーは冬の真夜中付近て発生頻度か高い.2)緯度的には夜間は地磁気緯度60°-75°,昼間ては70°-80°でよく観測される.3)f-tスペクトルの形状から大きく分けて,双曲線状のものとV字形のものがある.4)ソーサーの発生領域はプラスマポースの外側て,VLFヒスの領域の低緯度側,またその発生源は1000-1500km以上の高度に存在していると考えられる. Characteristics of the saucer emissions are studied by using ISIS VLF data which were received at Syowa Station by the wintering party of the 17th Japanese Antarctic Research Expedition in 1976-1977. Saucers were observed most frequently in the nighttime in winter and were scarcely observed in summer, The magnetic latitude ranges in which saucers were observed are ～60゜-75° in the nighttime and ～70°-80゜ in the daytime. These occurrence regions are located at the higher latitude side of the plasmapause and at the lower latitude side of the hiss occurrence regions. The shapes of saucers on frequency-time spectra showed generally two different types,i e, symmetrical hyperbolic shapes and symmetrical V-shapes departmental bulletin paper